2022
DOI: 10.1097/qai.0000000000002877
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Electrocardiographic Abnormalities in Adults With HIV: Insights From the Randomized Trial to Prevent Vascular Events in HIV (REPRIEVE)

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…Additional study is needed from across the region to determine whether the high burden of prior MI and myocardial ischemia observed via ECG in PWH in Tanzania is representative of other countries in the region. Notably, the prevalence of ischemic ECG findings observed among PWH in our study is higher than reported in a globally representative low-moderate risk HIV infected population, but similar to what has been reported in older-aged cohorts from Europe and North America [28,29]. The fact that we observed a similar prevalence of ischemic ECG findings in a younger cohort in Tanzania raises the possibility that other factors, such as cardiomyopathies, malnutrition, and poorly-controlled hypertension, may be contributing to the abnormal ECG findings in our study population.…”
Section: Discussionsupporting
confidence: 87%
“…Additional study is needed from across the region to determine whether the high burden of prior MI and myocardial ischemia observed via ECG in PWH in Tanzania is representative of other countries in the region. Notably, the prevalence of ischemic ECG findings observed among PWH in our study is higher than reported in a globally representative low-moderate risk HIV infected population, but similar to what has been reported in older-aged cohorts from Europe and North America [28,29]. The fact that we observed a similar prevalence of ischemic ECG findings in a younger cohort in Tanzania raises the possibility that other factors, such as cardiomyopathies, malnutrition, and poorly-controlled hypertension, may be contributing to the abnormal ECG findings in our study population.…”
Section: Discussionsupporting
confidence: 87%
“…Our study also found the odds of QTc interval prolongation increased by 7% for every year increase in age. Apart from aging, ethnicity might play a role as supported by the result of REPRIEVE study that Asian PWH had two time higher odd of prolonged QTc than other ethnicities [30].…”
Section: Discussionmentioning
confidence: 94%
“…One recent study reported a 1.6% incidence of new QT prolongation within 2 years among virally suppressed PLWH [71 ▪ ]. Relatively high prevalences of early repolarization abnormalities (12.4%) and electrocardiographic left ventricular hypertrophy (8.3%) were also recently reported in the multinational Randomized Trial to Prevent Vascular Events in HIV (REPRIEVE) Study [66 ▪ ]. While studies in the general population suggest the association between electrocardiographic early repolarization [72] and left ventricular hypertrophy with SCD [73], long term clinical follow-up is required to determine clinical significance in PLWH (Table 2).…”
Section: Subclinical Disease Measures and Risk Of Ventricular Arrhyth...mentioning
confidence: 87%
“…Several studies report longer absolute corrected QT and QT subcomponent intervals among PLWH versus controls, both in developed and low income countries [64,65,66 ▪ ,67,68,69 ▪ ]. Risk factors for prolonged QT in PLWH include male sex [66 ▪ ], Asian race [66 ▪ ], high HIV viral load [63,65,66 ▪ ], lower CD4 count [63,65], ART use [69 ▪ ], and increased inflammatory biomarker levels [64,68]. The data correlating specific ART classes and QT prolongation are conflicting but support increased risk with older generation protease inhibitors, efavirenz, and rilpivirine [65,70].…”
Section: Subclinical Disease Measures and Risk Of Ventricular Arrhyth...mentioning
confidence: 99%
See 1 more Smart Citation